Can Islet Transplantation Possibly Reduce Mortality in Type 1 Diabetes - Jeffrey S. Isenberg; Fouad Kandeel (Cell Transplantation)
Islet transplantation (IT) is a successful natural cell therapy. But the benefits are known mostly to individuals with severe type 1 diabetes who undergo IT and the health care professionals that work to make the therapy available, reproducible, and safe. Data linking IT to overall survival in T1D might alter this situation and frame the therapy in a more positive light. Recent analysis of mortality in several cohorts suggests that IT has possible survival benefits when used alone or in conjunction with renal transplantation. Multi-center prospective studies with long-term follow-up of individuals that receive stand-alone IT versus individuals who qualify for but do not undergo the procedure would seem reasonable to undertake to confirm an IT survival benefit.